Histone methyltransferase Dot1L is a coactivator for thyroid hormone receptor during Xenopus development - Wen, Luan (FASEB J, 2017)
Histone modifications are associated with transcriptional regulation by diverse transcription factors. Genome-wide correlation studies have revealed that histone activation marks and repression marks are associated with activated and repressed gene expression, respectively. Among the histone activation marks is histone H3 K79 methylation, which is carried out by only a single methyltransferase, disruptor of telomeric silencing-1–like (DOT1L). We have been studying thyroid hormone (T3)-dependent amphibian metamorphosis in two highly related species, the pseudo-tetraploid Xenopus laevis and diploid Xenopus tropicalis, as a model for postembryonic development, a period around birth in mammals that is difficult to study. We previously showed that H3K79 methylation levels are induced at T3 target genes during natural and T3-induced metamorphosis and that Dot1L is itself a T3 target gene. These suggest that T3 induces Dot1L expression, and Dot1L in turn functions as a T3 receptor (TR) coactivator to promote vertebrate development. We show here that in cotransfection studies or in the reconstituted frog oocyte in vivo transcription system, overexpression of Dot1L enhances gene activation by TR in the presence of T3. Furthermore, making use of the ability to carry out transgenesis in X. laevis and gene knockdown in X. tropicalis, we demonstrate that endogenous Dot1L is critical for T3-induced activation of endogenous TR target genes while transgenic Dot1L enhances endogenous TR function in premetamorphic tadpoles in the presence of T3. Our studies thus for the first time provide complementary gain- and loss-of functional evidence in vivo for a cofactor, Dot1L, in gene activation by TR during vertebrate development.—Wen, L., Fu, L., Shi, Y.-B. Histone methyltransferase Dot1L is a coactivator for thyroid hormone receptor during Xenopus development.